2022
DOI: 10.1371/journal.pone.0278196
|View full text |Cite
|
Sign up to set email alerts
|

Partner alcohol consumption and intimate partner violence against women in sexual unions in sub-Saharan Africa

Abstract: Introduction Intimate partner violence is increasingly gaining attention as the leading form of violence against women globally, particularly sub-Saharan Africa. Given that substance abuse, especially alcohol consumption has long been associated with aggressive behaviour, emotional abuse, and sexual misconduct, it is surprising that studies on the potential association between partner’s alcohol consumption and intimate partner violence are scarce. The current study seeks to fill this gap in the literature by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A study in India showed that women who experienced their father beating their mother were more likely to accept violence [46]. Witnessing violence during childhood may result in normalization or acceptance of violence by women [41]. Childhood experiences of violence at home reinforce normative form of violence for both men and women which subsequently increases the likelihood of perpetration for men and acceptance for women [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in India showed that women who experienced their father beating their mother were more likely to accept violence [46]. Witnessing violence during childhood may result in normalization or acceptance of violence by women [41]. Childhood experiences of violence at home reinforce normative form of violence for both men and women which subsequently increases the likelihood of perpetration for men and acceptance for women [47].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies link partner's alcohol use with perpetration of violence. [39][40][41] . Alcohol consumption is linked with aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most highly reported consequences of partner's alcoholism are the emotional problems, the least reported are the problems of physical violence (Govindappa & Pankajakshi, 2014;Sharma et al, 2016;Sreekumar et al, 2016). Partner's alcohol consumption increases women's likelihood of experiencing emotional, sexual and physical violence (Aboagye, 2022;Sontate et al, 2021). Women are reported to be twice as likely to experience physical abuse, including potentially fatal injuries, as a result of alcoholrelated domestic violence (Ferrari, 2018;Galbicsek, 2020;Myshak et al, 2020).…”
Section: Alcoholism Of Partner and Violence Against Womenmentioning
confidence: 99%
“…There is extremely low health seeking behavior amongst women who had been subjected to IPV; only 38.8% of these women seek for help in sub-Saharan Africa [36]. Patriarchal norms and values such as gender roles and expectations of women by society have also been reported to prevent women from seeking help for IPV [15].…”
Section: Health Related Outcomesmentioning
confidence: 99%